Beyond Awareness: Investigating How Moral Obligation Strengthens the Impact of Environmental Knowledge on Green Purchase Intention - Firza, Edy; Meilinda Dwi Anugrah; Kurnia Widya Oktarini; Ulfah Tika Saputri; Devi Febrianti (LPPM Universitas Jambi, 2025)
This study investigates the effect of environmental knowledge on green purchase intention and examines the moderating role of moral obligation in this relationship. A quantitative research design was employed using a survey approach. Data were gathered through an online questionnaire administered to 512 individuals who have prior experience considering or purchasing environmentally friendly products. The analysis was conducted using SmartPLS version 4. The results reveal that environmental knowledge exerts a positive and significant influence on green purchase intention. In addition, moral obligation significantly moderates this relationship. Specifically, the impact of environmental knowledge on purchase intention becomes stronger when individuals possess a heightened sense of moral responsibility toward environmental preservation. These findings support existing literature by highlighting the interplay between cognitive factors (knowledge) and moral considerations in shaping sustainable consumption behavior. The study also emphasizes the importance of combining educational efforts with ethical awareness in developing effective green marketing strategies.